Pengaruh Perencanaan dan Pengawsan Terhadap Penerapan Anggaran Berbasis Kinerja Pada SKPD di Kabupaten Gorontalo - Mattoasi, Mattoasi; Monoarfa, Valentina; Hasan, Nurul Aulia (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2024)
This research aims to determine the influence of planning and supervision on the implementation of performance-based budgeting in SKPD in Gorontalo Regency, either partially or simultaneously. This research uses quantitative research methods. The data source used in this research is primary data obtained from questionnaires distributed to the population in this study, namely all Regional Work Units (SKPD) in Gorontalo Regency which are directly involved in managing and producing PAD using Purposive Sampling. The data analysis technique in this research is descriptive quantitative analysis using the statistical t test, statistical f test, and coefficient of determination test (Adjusted R Square) using IBM SPSS 26 for windows. The results of the research show that Planning and Supervision has a positive and significant effect on the implementation of performance-based budgeting in SKPD in Gorontalo Regency both partially and simultaneously with a determinant value of 38.6% while the remaining 61.4% is explained by other variables not studied. in this research.